2013
DOI: 10.1539/joh.12-0231-oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Psychological Violence and Harassment at Work: Reliability and Validity of the Japanese Version of the Inventory of Violence and Psychological Harassment (IVAPT) Comparing NAQ‐R and LIPT

Abstract: Terrorization (LIPT) and Negative Acts QuestionnaireRevised (NAQ-R), and psychological harassment at work was well concordant with the NAQ-R. Conclusions: The Japanese version of the IVAPT showed high internal consistency reliability. While the first factor explained a large proportion of the variance, the IVAPT seems to have a unique factor structure in the Japanese sample. Concurrent validity of the IVAPT was supported by the comparison with the other scales. Psychological harassment at work, also called as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 10 publications
0
18
1
2
Order By: Relevance
“…Although workplace bullying is a particularly sensitive topic, overall response rate in the present study was high (73.4%) as compared with the results of other studies that ranged from 38.5% to 68% [13] , [28] , [29] , [30] .…”
Section: Discussioncontrasting
confidence: 70%
“…Although workplace bullying is a particularly sensitive topic, overall response rate in the present study was high (73.4%) as compared with the results of other studies that ranged from 38.5% to 68% [13] , [28] , [29] , [30] .…”
Section: Discussioncontrasting
confidence: 70%
“…The remaining 10 studies within the review used previously validated measurement tools. The Negative Acts Questionnaire—Revised (NAQ‐R) was used in six studies 9,20,22,28,29,39 . Each study focused on different psychometric qualities of the NAQ‐R.…”
Section: Resultsmentioning
confidence: 99%
“…For two of the remaining papers, this was the first published article of the identified measurement tool. These were the Inventory of Violence and Psychological Harassment (IVAPT) by Moreno et al 26 and the Civility Norms Questionnaire Brief (CNQB) by Walsh et al 32 The final two papers with validated measures also linked to other measurement tools in the review. The study by Martin and Hine 25 developed the Uncivil Workplace Behaviour Questionnaire (UWBQ) which was contrasted within this study with the Workplace Incivility Scale (WIS) 40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the NAQ-R contains three factors, an analysis has shown that all of the items within these factors load onto one factor that has a high Cronbach alpha value of 0.90, which supports its use as a single factor measure [14]. The NAQ-R has been shown to be a valid and reliable measures in diverse workplace settings [36,[67][68][69][70]. It consists of 22 items, each of which is scored on a five point Likert scale ranging from 1-5.…”
Section: Methodsmentioning
confidence: 91%